2019
DOI: 10.17576/jsm-2019-4811-18
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Geoasset Exploration in Bukit Besi for Geotourism Development: A Preliminary Study

Abstract: Geotourism is a responsible and sustainable type of tourism package development, equivalent to ecotourism, and other nature-based derivatives of tourism with deeper level considerations on local landscapes and the underlying geological foundation. The area was investigated from the perspective of tourism geoscience sub-discipline with a focus on nonextractive natural resources. Taking into consideration the beach alluvial plain, human community, the biophysical components and the mining artifacts, mineralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For example, currently, the research on the mining industry in Malaysia is conducted on ex-tin mining to study the impact on environmental and social activities as reported by Sanusi et al (2017), Sakai et al (2017), Ahmed et al (2018), Sanusi et al (2021), Shahbudin et al (2021), andLehmann et al (2021). Moreover, Sarman et al (2019) conducted research on iron ore mining, concentrating on the potential of geotourism for ex-iron ore mines in Bukit Besi, Dungun, Terengganu. Meanwhile, Tohar et al (2020) studied the potential of major rare earth-bearing minerals in Johor, Malaysia's southern peninsula.…”
Section: Future Outlook For Malaysian Mining Industrymentioning
confidence: 99%
“…For example, currently, the research on the mining industry in Malaysia is conducted on ex-tin mining to study the impact on environmental and social activities as reported by Sanusi et al (2017), Sakai et al (2017), Ahmed et al (2018), Sanusi et al (2021), Shahbudin et al (2021), andLehmann et al (2021). Moreover, Sarman et al (2019) conducted research on iron ore mining, concentrating on the potential of geotourism for ex-iron ore mines in Bukit Besi, Dungun, Terengganu. Meanwhile, Tohar et al (2020) studied the potential of major rare earth-bearing minerals in Johor, Malaysia's southern peninsula.…”
Section: Future Outlook For Malaysian Mining Industrymentioning
confidence: 99%